CRISP Spectropolarimetric Imaging of Penumbral Fine Structure - Scharmer, G. B; Narayan, G; Hillberg, T; de la Cruz Rodriguez, J; Löfdahl, M. G; Kiselman, D; Sütterlin, P; van Noort, M; Lagg, A (Astrophysical journal. Letters, 2008)
We discuss penumbral fine structure in a small part of a pore, observed with the CRISP imaging spectropolarimeter at the Swedish 1-m Solar Telescope (SST), close to its diffraction limit of 0.16 super([image] ). Milne-Eddington inversions applied to these Stokes data reveal large variations of field strength and inclination angle over dark-cored penumbral intrusions and a dark-cored light bridge. The mid-outer part of this penumbra structure shows [image]0.3 super([image] ) wide spines, separated by [image]1.6 super([image] ) (1200 km) and associated with 30 degree inclination variations. Between these spines, there are no small-scale magnetic structures that easily can be identified with individual flux tubes. A structure with nearly 10 degree more vertical and weaker magnetic field is seen midway between two spines. This structure is cospatial with the brightest penumbral filament, possibly indicating the location of a convective upflow from below.